Platform Pricing Structure and Moral Hazard. Issue 3 (September 2014) - Roger, Guillaume; Vasconcelos, Luís
<x xml:space="preserve">Abstract</x> We study pricing by a two‐sided platform when it faces moral hazard on the sellers' side. In doing so, we introduce an equilibrium notion of platform reputation in an infinite horizon model. We find that with transaction fees only, the platform cannot eliminate the loss of reputation induced by moral hazard. If registration fees can be levied, moral hazard can be overcome. The registration fee determines the participation threshold of sellers and extracts them, whereas (lower) transaction fees provide incentives for good behavior. This provides a motivation for platforms to use registration fees in addition to transaction fees.